RISE OF CHINA AND THE EU RESPONSES: THE SEARCH OF NEW TRENDS IN CONTEMPORARY HISTORY (Journal of European Studies (JES), 2017)
This paper contextualizes Chinese economic ascent in the broader framework of multipolarity. Chinese ruling elites have always disdained the vanity of strength. They like to enhance their influence through subtle bargaining and consensus. The communist leadership since the time of Deng Xiaoping has deliberately taken a commercial posture and presented China as a business-friendly power. Recent efforts towards greater connectivity (the One Belt One Road) represent the continuation of that trend. The author holds that the European Union and China support a multipolar and commercially connected world. Therefore, the rise of China augurs peace and material prosperity in its immediate periphery as well as in Eurasia. The emerging trends do not signal confrontation and hostility with the West.